The role of cyberslacking in student performance - Devara Windya Fadhila; Muafi (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2025)
Internet access in universities facilitates students' learning. However, students often use the internet during class for non-academic activities such as social media, games, or shopping. This behavior, known as cyberslacking, can cause students to lose focus and lower their academic performance. This study aims to investigate the effects of media multitasking efficacy and technostress on cyberslacking and academic performance. The study used a quantitative method with 270 management students at Universitas Islam Indonesia. Data were collected through questionnaires and analyzed using PLS-SEM. The results of this study showed that media multitasking efficacy negatively affected cyberslacking, while technostress positively affected it. Additionally, cyberslacking adversely affected academic performance. The findings also revealed that media multitasking efficacy had a positive impact on educational achievement, with cyberslacking as a mediator.